Respostas

2013-05-23T19:42:30-03:00

A)

x²+x²-6x=0

2x²-6x=0

raiz de delta= 6²-4*2*0

delta=36

raiz de delta=6

x1= 6+6/2*2=12/4=3

x2= 6-6/2*2=0/4=0

 

B) x²-3x-2x+6=6

x²-5x=0

raiz de delta= 5²-4*1*0

delta=25

raiz de delta=5

x1= 5+5/2=5

x2= 5-5/2=0/2=0

 

C) x²-4x+4=4-9x

x²+5x=0

raiz de delta= 5²-4*1*0

delta=25

raiz de delta=5

x1=-5+5/2=0/2=0

x2= -5-5/2=-10/2=-5

 

4 4 4
A melhor resposta!
2013-05-23T20:13:02-03:00

Olá!!!!

 

a) x² +x(x - 6)=0   distribuindo

 

2x² - 6x=0

 

2x(x-3) = 0  >>>>>>>>> x = 0    ou    x=3

 

 

 

b) x(x-3)-2(x-3)=6 efetuando a distributiva  e cancelando o +6

 

x²-3x-2x+6=6

 

x²-5x=0 

 

x(x-5)=0>>>>>>>>>>>>x=0  ou   x=5

 

 

c)(x-2)²=4-9x

 

c) x²-4x+4=4-9x   cancelando 4

 

  x²-4x+9x=0

 

  x²+5x=0

 

   x(x+5)=0 >>>>>>>x=0   ou  x= -5

 

 

d)(x+1) (x-3)= -3

 

x²-2x-3=-3  cancelando - 3

 

x²-2x = 0

 

x(x-2) =0  >>>>>> x=0   ou   x= 2

 

 

veja se entendeu!!!

7 4 7